2020
DOI: 10.2147/rmhp.s256656
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence and Use of Dietary Supplements Among Pharmacy Students in Saudi Arabia</p>

Abstract: Purpose Dietary supplements (DSs) are popular in many countries, and their use among individuals is increasing worldwide. Therefore, this study aimed to assess the prevalence and use of DSs among pharmacy students in King Saud University College of Pharmacy, Riyadh, Saudi Arabia. Methods This study used a cross-sectional design targeting male senior pharmacy students in their fourth and fifth years of Bachelor and Doctor of Pharmacy courses. The data were collected betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 41 publications
7
31
0
1
Order By: Relevance
“…Multivitamins/minerals (56.8%) were the most frequently used among Mediterranean people [ 12 ]. Similar findings were also reported in Gulf countries, including Kuwait [ 1 ], the United Arab Emirates [ 3 ], and Saudi Arabia [ 7 , 8 , 9 ]. Advice from health care workers was the most frequently cited reason for using dietary supplements.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Multivitamins/minerals (56.8%) were the most frequently used among Mediterranean people [ 12 ]. Similar findings were also reported in Gulf countries, including Kuwait [ 1 ], the United Arab Emirates [ 3 ], and Saudi Arabia [ 7 , 8 , 9 ]. Advice from health care workers was the most frequently cited reason for using dietary supplements.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, a survey in the USA including participants from Hawaii and Los Angeles, California, showed that dietary supplement use amounted to 44% among Hawaiian males and 75% among Japanese American and White females [ 6 ]. Likewise, in Saudi Arabia, high figures were reported, amounting to 76.6% among female college students in Riyadh [ 7 ], 46.8% among pharmacy students [ 8 ], 30% among Dammam university students [ 9 ], and 26.2% among adolescent school children [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies from Saudi Arabia have shown the increased prevalence of DS use among its population. However, these studies recommend the consumers to use it with a doctor’s prescription and advocates for increased awareness about its health effects [ 17 , 18 ]. Studies have demonstrated the positive health effects of functional foods on respiratory, viral and parasitic, infectious, and inflammatory diseases [ 19 ].…”
Section: Introductionmentioning
confidence: 99%